Nietzsche and the aristocrats of work - Faro, Giorgio (Acta Philosophica, 2024)
This essay aims to dwell on the peculiar conception of artistic work in Nietzsche, the only work that Nietzsche appreciated, in the youthful phase of his works (up to Human, Too Human), for the saving role of aesthetics (especially music), which is meant to conceal the tragic aspect of reality. After the disappointment caused by the ‘Wagner case’, there will be an Enlightenment phase, in which science will seem to take the place of artistic work. However, by Thus I Speak Zarathustra, the mature Nietzsche will once again return to consider aesthetic enjoyment as man’s only salvation against the tragic pessimism that reality incites, considering even science an illusion. There will be no shortage of comparisons with Thomas Mann’s novel Doctor Faustus, with Marx, Dostoevsky, Kierkegaard, van Gogh and a final review of Nietzsche’s proposal.